Diagnosing glaucoma in optometry practice - A.V. Korneeva; I.N. Isakov; A.V. Kuroyedov; O.N. Onufriichuk (РМЖ "Клиническая офтальмология")
A.V. Korneeva1, I.N. Isakov2, A.V. Kuroedov3,4, O.N. Onufriychuk5 1LLC "Ophthalmology Elite", Moscow, Russian Federation 2G.B. Kurbatov Novokuznetsk City Clinical Hospital No. 1, Novokuznetsk, Russian Federation 3Pirogov Russian National Research Medical University, Moscow, Russian Federation 4P.V. Mandryka Military Clinical Hospital, Moscow, Russian Federation 5G.I. Turner National Medical Research Center of Сhildren’s Orthopedics and Trauma Surgery, St. Petersburg, Russian Federation The article discusses the role of optometry practice in diagnosing early glaucoma in the context of the obviously increasing incidence of glaucoma and the ophthalmic staffing shortage. It elucidates the findings of domestic and international studies focused on the early glaucoma diagnosis in optometry. The evolving role of optometry personnel in the public health system is underpinned by the increasing number of patients with eye diseases and the growing demand for primary ophthalmic care due to a higher life expectancy of the population. So far, the optometry practice is not always considered as a part of the public health system, but it plays an important role in protecting the vision, as it often helps to identify patients with early stages of refractive disorders and other ophthalmic diseases. The opportunities of diagnosing of glaucoma in optometric practice usually depend on the set goals, available equipment, optometrist skills and commitments to achieving the results. Improving equipment availability in the optometrist’s office, professional development of specialists and their motivations for performing diagnostic tes ts may optimize the detection of glaucoma. It is also worth noting the importance of interaction between the optometrist and the ophthalmologist. Over the past years, a positive trend to optometry development has emerged shaping the future expansion of the scope of traditional professional interests of optometry staff. The trend is based on the improved situation with the equipment availability and the professional development of specialists. Keywords: glaucoma, optometrist, optometry practice, ophthalmologist, glaucoma diagnostics, glaucoma optic neuropathy. For citation: Korneeva A.V., Isakov I.N., Kuroedov A.V., Onufriychuk O.N. Diagnosing glaucoma in optometry practice. Russian Journal of Clinical Ophthalmology. 2022;22(4):258–264 (in Russ.). DOI: 10.32364/2311-7729-2022-22-4-258-264.